When is the smile categorized as an orthodontic smile? Highlight of a new conceptualization - Dias, Maria do Rosário; Neves, Ana Cristina (MedCrave, 2024)
Objective: Pioneering studies were conducted at a Dental University Clinic, focusing on the mental representation of the smile in patients with orthodontic braces. This brief communication presents the final findings from several studies that emphasize the significance of self-perception of the mouth and smile in shaping self-image and well-being across children, adolescents, and adults. Drawing was employed as a projective tool and graphic recording method, within the framework of a highly empirically relevant methodology.Methods: The sample was composed of two groups of patients of feminine and masculine gender, G1 - children and young people (8-24 Y) and G2 - Adults (25-59 Y), who underwent treatment with orthodontic appliances at the Orthodontic consultation. Participants were invited to draw two drawings of their mouth/smile based on the following questions: “What was your mouth like before you got braces?” (M1); and “What do you think your mouth will look like when you remove your braces?” (M2). The content analysis of all drawings made was carried out using a grid composed of analytical categories and subcategories. A sociodemographic questionnaire was also carried out, with the question, “Why do you wear orthodontic braces?”Results: Differences were found in the scope of the mental representation of the mouth and smile, and of expression of smile emotions. Conclusion: The results suggest that functional are the main reason for young people (children and adolescents) seeking orthodontic treatment, while adult participants appear to be motivated by aesthetic reasons.
Keywords: Orthodontic smile; Mental representation of smile; Orthodontic treatment; Children and adolescents